Environmental Development, Improving Creative Economy, and Education in Banjarsari Village: Pengembangan Lingkungan, Peningkatan Ekonomi Kreatif, dan Edukasi di Desa Banjarsari - Permatasari , Putri; Ambarwati , Rita; Sa’adah , Inzani Nur; Mawardi , Indrianingsih; Faujiah , Silmida (Universitas Muhammadiyah Sidoarjo, 2022)
The implementation team of Community Service Activities by students in Banjarsari Village, Buduran District carried out three work programs including the Environment, Creative Economy and Educational programs. The problems faced are the lack of a caring attitude towards the environment, the lack of forums in the field of entrepreneurship around Banjarsari Village and the passive education of children. The goal is to build motivation, the community to create a cool environment while developing the creative economy and increasing awareness of the importance of education in early childhood, then problem solving in this research can be done by providing knowledge, understanding and behavioral training.